Opportunism in Corporate Management - Rudolf, Stanislaw (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
A growing interest in the phenomenon of economic opportunism can be mainly explained by new institutional economics (NIE). It has changed the limitation of that phenomenon into the main method of increasing the efficiency of business entities. Opportunistic attitudes and behaviour can be particularly observed in a business entity. A tendency towards opportunism should be considered both while entering contracts and while developing a strategy for a company. The article is aimed at presenting the essence of opportunism and at defining its place in new institutional economics. It is also aimed at identifying opportunistic attitudes in corporate operation and at indicating the ways to limit such attitudes. While analysing the role of opportunism in corporate management, the main focus shall be set on opportunistic interdependencies in corporate governance. Opportunistic attitudes may be presented not only by the management board of a company but also by its other stakeholders. They may use incompleteness of agreements that have been entered into or asymmetry of information in order to increase their gain at the expense of others. The article provides a more detailed analysis of opportunistic attitudes presented by employee organisations in highly developed countries as well as in post‑communist countries, where opportunism is manifested in demanding attitudes or in protection of monopolist positions.